Driving mechanisms of taxonomic and functional community composition of Collembola during subalpine succession - Yan Zhang; Ajuan Zhang; Zheng Zhou; Ting-Wen Chen; Xueyong Pang; Stefan Scheu (Geoderma)
Plant succession dramatically alters both aboveground vegetation and belowground conditions, impacting the organisms residing in the soil. However, the extent to which the taxonomic and functional community composition of soil animals is shaped by the same biotic and environmental factors and their relative importance remains unclear. Here, we considered plant community characteristics, abiotic soil factors, and food-web factors as potential drivers for the taxonomic and functional community composition (based on life forms) of Collembola during plant succession in the subalpine region of southwest China. Our results show that Collembola abundance and richness were lower in grassland, shrubland, and primary forest compared to secondary forest (birch forest). Temperature and moisture were identified as pivotal factors influencing Collembola fitness in grassland, while soil pH was a key factor in primary forest. Overall, abiotic soil factors (i.e., pH, C/N, and temperature), played predominant roles in shaping both the taxonomic and functional community composition of Collembola. Plant community characteristics (i.e., plant richness and litter biomass) were subdominant drivers in structuring functional community composition. By contrast, food-web factors (i.e., fungal biomass and fungi-to-bacteria ratio as bottom-up factors, and predatory mites as top-down factor) exerted a minor impact. Further, functional community composition was generally more closely related to variations in soil abiotic factors and plant community traits than taxonomic community composition. These findings highlight the priority importance of soil abiotic factors over plant community characteristics and food web factors in structuring soil mesofauna communities and emphasize the importance of trait-based approaches for understanding the mechanisms underlying soil animal communities.